Evaluating the Peer Education Project in secondary schools. Issue 1 (14th January 2019) - Eisenstein, Carin; Zamperoni, Victoria; Humphrey, Neil; Deighton, Jessica; Wolpert, Miranda; Rosan, Camilla; Bohan, Helen; A. Kousoulis, Antonis; Promberger, Marianne; Edbrooke-Childs, Julian
Abstract : Purpose: The purpose of this paper is to determine the efficacy of the Peer Education Project (PEP), a school-based, peer-led intervention designed to support secondary school students to develop the skills and knowledge they need to safeguard their mental health and that of their peers. Design/methodology/approach: Six schools from across England and the Channel Islands took part in an evaluation of the PEP across the 2016/2017 academic year. In total, 45 trained peer educators from the sixth form and 455 Year 7 students completed pre- and post-questionnaires assessing their emotional and behavioural difficulties, perceived school climate, and knowledge, skills and confidence related to mental health. Findings: Results indicate that participation in the PEP is associated with significant improvement in key skills among both peer educators and student trainees, and in understanding of key terms and readiness to support others among trainees. Most students would recommend participation in the programme to other students. Originality/value: While peer education has been found to be effective in some areas of health promotion, research on the effectiveness of peer-led mental health education programmes in schools is limited. This study contributes evidence around the efficacy of a new peer education programme that can be implemented in secondary schools.